GROWTH AND SURVIVAL RATE OF THE DAMSELFISH (Anabas testudineus ) WITH DIFFERENT STOCKING DENSITY - Rizka Syulfia; Iskandar Putra; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on June 1 until July 15, 2015 in Aquaculture Technology Laboratory. The aim of research to determine the growth rate and survival rate of fish damselfish (Anabas testudineus) with different stocking density. This study uses a completely randomized design (CRD) with a factor of three levels of treatment, each level of treatment replications performed three times. The treatment given is Betok fish stocking density 15 fish / container or 300 fish / m3, 20 fish / container or 400 fish / m3 and 25 tails / container or 500 fish / m3. To know the development of fish, every 15 days were measured body weight and total length. Observations indicating that the growth and survival of fish damselfish (Anabas testudineus) with different stocking density was not significantly different with the absolute growth of fish, the absolute length growth, and daily growth rate, but significantly different to the survival of fish. The best results in this study is in treatment P3 with a stocking density of 25 fish. At the treatment resulted in the growth of the absolute weight of 2.27 grams, the absolute length of 2.02 cm, the daily growth of 0.96% and was significantly different to the SR of 77%.Keywords : Growth , Survival, Betok (Anabas testudineus), Stocking Density